Forest (Conservation) Act-Implications of Provisions Requiring Policy Intervention for Effective Implementation - Gangwar, Prachi; Sinha, D. P. (Indian Forester, 2017)
Forest (conservation) Act, 1980 was enacted to check indiscriminate diversion of forest land. The objective of the act is to regulate diversion of forest land for non forest purpose. The paper analyses the provisions, implications and implementation of the Act based on study of several cases. The Act which is probably the smallest in the country, has to its credit highest number of guidelines, clarifications and instructions, which makes it complex if not confusing. Some of the clarifications/instructions/guidelines appear to be against the spirit of the Act. In this paper cases have been examined, where gross violation of FCA has taken place due to negligence, lack of will power to take action, and sometimes ignorance of facts or provisions of the Act. Implications of non compliance of conditions, imposed in the approval granted under FCA, have also been critically examined. Mutation of non forest land, provided for compensatory afforestation in lieu of forest land diverted, and subsequently declaration of such land as ’Forest’ is a major challenge. This eventually defeats the very purpose of the Act, which was to compensate for the loss of forest land. Lack of clarity and procedure in the penal clause for violation of the provisions of Forest (Conservation) Act comes into way in invoking the penal clause and thus makes it ineffective. Certain other provisions of the Act have also been dealt with in the paper. These provisions/clauses, if suitably amended/enacted, would render more adequacy and efficacy to the Act.